Efektivitas Pembelajaran Literasi Melalui Kartu Domino Untuk Hasil Belajar Perkembangan Motorik Pada Mahasiswa - Ratno Susanto; Ronald Dwi Ardian Fufu; Al Ihzan Tajuddin; Salmon Runesi (Jurnal Ilmiah STOK Bina Guna Medan, 2024)
The purpose of this study is to demonstrate that using domino media cards can improve third semester student learning outcomes. The study's findings indicate that student learning attainment increases when using domino media, with a rata-rata of approximately 77. A good motor skill is very important for both physical and mental health. Malays with good motor skills tend to be more active in their physical activities, which can improve their overall health. Education at all levels should incorporate motor skills instruction into their curricula, especially in programs related to health, sports, and humanities. This method uses the deskriptif kualitatif method. The study is conducted with two groups: one group that uses the domino game in class and one group that does not use the game. Comparing the learning outcomes of both groups using tes before and after intervention. Data is gathered via a questionnaire that reduces student perceptions on the effectiveness of domino games in terms of increasing the target audience. Playing domino games in groups can promote physical activity, such as pushing or shoving cards across the room, which can help with the development of kasar motor impairment. Playing dominoes in a group setting fosters interpersonal and professional relationships among players. This not only increases social reactivity but also stimulates physical activity that can slow down the rate of motor neuron degeneration. The study's findings indicate that this medium is very feasible to utilize, with 91.99% presentation suitability and 98% content suitability according to subject matter experts. It also appears that the improvement in outcomes from classroom trials is substantial. In summary: Utilizing domino cards in conjunction with motor development courses to enhance third semester students' literacy abilities.